Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale. (January 2023) - Wong, Tin-Long; Li, Li-Feng; Zhang, Ji-Xia; Zhang, Quan-Wei; Zhang, Xue-Ting; Zhou, Li-Shuang; Fung, Hau-Yee; Feng, Lei; Cheng, Hui-Yuan; Huo, Chu-Ying; Liu, Man; Bao, Wan-Rong; et al.
Abstract: The backbone of Dendrobium officinale polysaccharide (DOP) was reported to be glucomannan. But the dispute continues due to the limitation of conventional analysis methods (e.g., the overlapped NMR signals). Herein, we describe an oligosaccharide sequencing analysis that successfully corrects the backbone to mannan. This analysis involves producing oligosaccharide fragments from mild acid hydrolysis of DOP followed by p -aminobenzoic ethyl ester (ABEE) derivatization. Then, a series of oligosaccharides with varied polymerization degrees (DP = 2–10) were isolated and identified by LC-MS profiling, monosaccharide composition analysis, linkage analysis, and 1D-/2D-NMR elucidation. Finally, we conclude that the backbone of DOP is a β -D-1, 4-mannan which is confirmed by other analysis such as comparison with reference mannan. This oligosaccharide analysis is more straightforward and reliable by transforming the complicated polymers into oligomers which have more accurate and convincing MS and NMR data. Graphical abstract: Image 1 Highlights: An oligosaccharide analysis method was proposed to characterize the DOP. A series of oligomers and isomers from hydrolyzed DOP were isolated and identified. An LC-MS method was established to test the oligomers' sugar sequence. The backbone structure of DOP was corrected to be a β -D-1, 4-Mannan.